1996
DOI: 10.1172/jci118537
|View full text |Cite
|
Sign up to set email alerts
|

Therapy with oral clotrimazole induces inhibition of the Gardos channel and reduction of erythrocyte dehydration in patients with sickle cell disease.

Abstract: Pathologic water loss from sickle erythrocytes concentrates the abnormal hemoglobin and promotes sickling. The Ca 2 ϩ -activated K ϩ channel (Gardos channel) contributes to this deleterious dehydration in vitro, and blockade of K ϩ and water loss via this channel could be a potential therapy in vivo. We treated five subjects who have sickle cell anemia with oral clotrimazole, a specific Gardos channel inhibitor. Patients were started on a dose of 10 mg clotrimazole/kg/d for one week. Protocol design allowed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
150
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(157 citation statements)
references
References 35 publications
7
150
0
Order By: Relevance
“…The remaining non-polymerized free heme passes through the membrane of food vacuoles and also reaches the cytosol of the parasite (39 -42), where free heme may be efficiently decomposed by reaction with GSH (10,11). It is reported that oral CLT (single dose of 1 g) was absorbed rather efficiently, reaching a concentration in plasma of 2 M within 2-4 h of administration (43) without serious side effects, and easily diffused into erythrocytes (43,44). Therefore, CLT should be able to reach the parasite compartment, enabling production of stable heme-CLT complexes in both erythrocytes and parasites.…”
Section: Inhibition Of Gsh-dependent Heme Degradation By Clt-mentioning
confidence: 99%
“…The remaining non-polymerized free heme passes through the membrane of food vacuoles and also reaches the cytosol of the parasite (39 -42), where free heme may be efficiently decomposed by reaction with GSH (10,11). It is reported that oral CLT (single dose of 1 g) was absorbed rather efficiently, reaching a concentration in plasma of 2 M within 2-4 h of administration (43) without serious side effects, and easily diffused into erythrocytes (43,44). Therefore, CLT should be able to reach the parasite compartment, enabling production of stable heme-CLT complexes in both erythrocytes and parasites.…”
Section: Inhibition Of Gsh-dependent Heme Degradation By Clt-mentioning
confidence: 99%
“…[3][4][5][6][7][8][9] Clotrimazole disrupts cellular Ca 2+ homeostasis by releasing Ca 2+ from intracellular stores while inhibiting Ca 2+ influx and blocking IK channels. 7,[10][11][12][13][14][15] It is being evaluated clinically for the treatment of IK channel-driven erythrocyte dehydration in sickle cell dis- ease 16,17 and the treatment of secretory diarrheas that involve chloride secretion through IK channels. 18 Interest in clotrimazole as a potential antileukemic compound derives from the following observations.…”
Section: Introductionmentioning
confidence: 99%
“…Erythrocyte dehydration in sickle cell disease can be attributed partly to excessive K ϩ loss through IKCa1 channels that are activated by a rise in intracellular Ca 2ϩ during sickling (10). Clotrimazole and ICA-15451, two potent triarylmethane (TRAM) blockers of this channel, are in clinical trials for the treatment of sickle cell disease (11,12). In intestinal and airway epithelium cells, basolateral expression of the IKCa1 channel modulates apical water and Cl Ϫ secretion (13,14), and blockade of this channel by clotrimazole has been reported to ameliorate secretory diarrhea (15).…”
mentioning
confidence: 99%
“…In intestinal and airway epithelium cells, basolateral expression of the IKCa1 channel modulates apical water and Cl Ϫ secretion (13,14), and blockade of this channel by clotrimazole has been reported to ameliorate secretory diarrhea (15). However, the therapeutic usefulness of clotrimazole is seriously limited by its nanomolar affinity for cytochrome P450-dependent enzymes, especially CYP3A4 (the major xenobiotic metabolizing enzyme in human liver), which leads to a high incidence of side effects (11,16).…”
mentioning
confidence: 99%